An Analysis of Behavioral Accounting and Islamic Ethics toward the Effectiveness of Regional Government Information System (SIPD) Implementation - Auliya'i kholqillahil Karimah; Kholilah Nailul Ulya; Mashudi Mashudi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the influence of behavioral accounting and Islamic ethics on the effectiveness of the implementation of the Regional Government Information System (SIPD). The study is motivated by the importance of digital transformation in regional financial management, which is influenced not only by the quality of information technology but also by the behavior of government officials and the application of ethical values within public organizations. This research employed a qualitative approach using a case study design. Data were collected through interviews, observations, and document analysis involving officials directly engaged in the implementation of SIPD, including system operators, treasurers, and regional financial reporting officers. The findings indicate that the effectiveness of SIPD implementation is influenced by human resource readiness, positive attitudes toward technology, adaptability, and organizational support. Furthermore, the application of Islamic ethical values such as amanah (trustworthiness), honesty, responsibility, and justice plays a significant role in enhancing the transparency and accountability of regional financial management. Government officials with high ethical integrity tend to demonstrate greater discipline and optimize the use of SIPD more effectively than those with lower ethical awareness. The study concludes that the successful implementation of SIPD requires not only reliable technological infrastructure but also positive user behavior and the integration of Islamic ethical principles in regional financial management.